Entre o sofrimento e o (in)cansável movimento: as tensões vivenciadas por concursados-concurseiros à luz da contemporaneidade e da gestão gerencialista - Rocha, Bianca Gomes Lima da (2019)
Capitalist logic has accentuated consumption and more and more desires are enhanced and the idealization for better social positions is evident. Management management uses this as a way of transforming individuals into machines capable of generating increased efficiency and greater profits for companies. Simultaneously alienates, mobilizes and controls the individual. Some seek to evade this logic and find some comfort in public service as contractors, becoming stable under the Law. But stability, in the ephemeral and fluid context of the contemporary world, is a violation of movement, liquidity, and the disruption of the status quo. , eventually revealing itself in a social imaginary predestined for dissatisfaction. It is in this context that many tendered civil servants resume their studies to seek new approvals that can gradually satisfy their desires. This reveals the instability of the stable as a possible phenomenon to be analyzed, anchored in the context of contemporary society - drunk on instability, consumption, liquidity and ideological characteristics arising from management processes. In this sense, the present research, in a rhizomatic perspective, uses the cartographic methodology as a way to follow the processuality of the context that is inserted, aiming to identify the tensions capable of generating the tireless desire of the concursado-concurseiro for new approvals. In 2018, second semester, and 2019, first semester, we used social networks as a tool to analyze the context and reach of the subjects, following discussions and instigating debates. Secondly, we followed the investigations, through the disclosure of qualitative questionnaire, on Facebook and Whatsapp, with questions that explored the findings gathered in the field under study. In order to deepen the lines of cartography, we use the word cloud technique to help analyze the data obtained through the forty-four answers given by concursados-concurseiros. The results showed that stability is the main reason for entry and permanence in the public service. Moreover, they revealed that the search for new approvals, consistent with the ideological elements of managerial management, is related to the need for financial satisfaction (increased remuneration, consumption and the possibility of helping the family); professional (“dream” career, position consistent with academic background); and personal (more time for leisure, family, travel). The instability of the stable is thus revealed during the cartographic course. The data indicated that the concursados-concurseiros recognize the differences between the advantages existing in the public and private initiative. However, only a few would ask to be discharged if they received what they think is a good private job offer. Among the causes pointed to justify this low index are the insecurity and instability in the contemporary political and economic scenario and the effects generated by management.